A Cost-Saving Machine: Computing at the German Allianz Insurance Company. - Schlombs, Corinna (Information & Culture, 2017)
This article provides a close study of information processing at Allianz, a West German insurance company, in the two decades following World War II. It contributes an international perspective to the history of information by analyzing corporate information technology decisions outside the United States and by tracing exchanges about information technology between insurance managers in the United States and Germany. The article argues that Allianz managers, claiming that electronic information processing would reduce offi ce operating costs, meticulously sought to document these savings to legitimate their computer acquisition in an otherwise adverse economic and political climate.